Comparative study of retinal nerve fibre layer thickness in normal and glaucomatous human eyes as measured by optical coherence tomography - Jain, Ritu; Choudhary, Nupur (International Journal of Research in Medical Sciences, 2020)
Background: Glaucoma is a disease primarily associated with damage to the Retinal Ganglion Cell (RGC) bodies and axons, which causes characteristic patterns of Visual Field (VF) and changes in the appearance of the Optic Nerve Head (ONH). This Study Compares Nerve Fibre layer thickness in normal and Glaucomatous Human Eye. Methods: It is a case control observational study carried out in 100 patients in a tertiary eye care hospital in the department of ophthalmology in the period from 1st January 2019 to 30th June 2019. Results: The diagnostic ability for distinguishing between normal and glaucoma patients were same when authors consider average RNFL thickness and average GCC thickness. Diagnostic accuracy increases when authors consider both RNFL and GCC thickness. There was a significant difference in both RNFL and GCC thickness between normal and glaucoma patient (p<0.001). The mean deviation shows a significant correlation with all the parameters in eyes with glaucoma (<0.001). Conclusions: RNFL thickness as measured by OCT showed statistically significant correlation with glaucoma. RNFL seems to have higher sensitivity and specificity for the detection of early glaucoma. Diagnostic accuracy increases when we include other parameters like RNFL and visual fields.